2021
DOI: 10.1016/j.eclinm.2021.101010
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of an inactivated SARS-CoV-2 vaccine in healthy adults aged 18 years or older: A randomized, double-blind, placebo-controlled, phase 1/2 trial

Abstract: Background We aimed to assess the safety and immunogenicity of an inactivated vaccine against COVID-19 in Chinese adults aged ≥18 years. Methods This is an ongoing randomized, double-blind, placebo-controlled, phase 1/2 clinical trial among healthy adults aged ≥18 years in Henan Province, China. Participants ( n = 336 in 18–59 age group and n = 336 in ≥60 age group) were enrolled between April 12 and May 17 2020, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 52 publications
(77 reference statements)
1
27
0
Order By: Relevance
“…Recent studies reported that a third homologous dose showed a satisfying safety profile and higher immune response, including BNT162b2 mRNA vaccine, CoronaVac inactivated vaccine and BBIBP-CorV vaccine. 1 3 Additionally, heterologous prime-boost vaccination of ChAdOx1 nCoV-19 followed by BNT162b2 induced a higher neutralizing activity compared to two homologous doses of ChAdOx1 nCoV-19. 4 Until now, the effect of heterologous vaccination of recombinant protein subunit vaccine primed with two doses of inactivated vaccines has not been evaluated, and data along this line could provide further evidence in establishing future global boosting strategies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported that a third homologous dose showed a satisfying safety profile and higher immune response, including BNT162b2 mRNA vaccine, CoronaVac inactivated vaccine and BBIBP-CorV vaccine. 1 3 Additionally, heterologous prime-boost vaccination of ChAdOx1 nCoV-19 followed by BNT162b2 induced a higher neutralizing activity compared to two homologous doses of ChAdOx1 nCoV-19. 4 Until now, the effect of heterologous vaccination of recombinant protein subunit vaccine primed with two doses of inactivated vaccines has not been evaluated, and data along this line could provide further evidence in establishing future global boosting strategies.…”
mentioning
confidence: 99%
“… 1 Homologous BBIBP booster study showed 1- to 3-fold increase after the third dose (day 56) compared to the GMT level of around 80 after the second dose (day 28). 3 Homologous CoronaVac booster study uncovered an ~3-fold increase of GMT level from the second dose to the third dose. 2 After 14 days of homologous ChAdOx1 nCoV-19 boost, the GMT levels increased to 3.69 times as high as the levels at baseline.…”
mentioning
confidence: 99%
“…Another double-blind, placebo-controlled phase 1/2 clinical trial was conducted to evaluate the safety and immunogenicity of an inactivated SARS-CoV-2 vaccine formulated with or without alum adjuvant in Chinese adults aged ≥18 years. The results suggested that the inactivated vaccine was well tolerated and immunogenic in both younger and older adults with no detectable antibody responses in all placebo groups [22]. The vaccine adjuvanted with alum alone was compared with the yeast-expressed trimeric form of the RBD protein adjuvanted with a TLR7/8 agonist and alum formulation, termed as alum-3M-052.…”
Section: Aluminum-based Adjuvantsmentioning
confidence: 99%
“…The most common type of vaccine in these studies was viral vector, with the viral vectors used were adenovirus in 11 studies [17,22,23,26,29,33,34,36,39,40,54] and baculovirus in 2 studies [35,48]. Eighteen studies using vaccines with adjuvants: AlOH3/Algel-IMDG in 21 studies [18][19][20][27][28][29][30][31]35,45,48,51,52,[55][56][57]59,64,66,68,70], Matrix-M1 in three studies [21,63,74], AS03/CpG + Alum in one study [25], Af03/AS03 in one study [36], and MF59 in one study [42].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The second most significant domain that induced the 'some concern' was bias caused by deviations from the intended intervention (domain 2), in which 27 trials also appeared to have a probability of risk [24,33,37,44,[46][47][48]51,[53][54][55][58][59][60]62,64,[66][67][68][69][70][73][74][75][76][77]. Almost all of the bias on domain 2 is because of disclosure of the intervention, whether to patients and or the carer of the patients.…”
Section: Adherence To Consort Recommendationsmentioning
confidence: 99%